Benefit from surgery with additional radiotherapy in N1 head and neck cancer at the time of IMRT: A population-based study on recent developments - Evers, Christoph; Ostheimer, Christian; Sieker, Frank; Vordermark, Dirk; Medenwald, Daniel (PloS one, 2020)
Currently, the role of adjuvant irradiation in head and neck cancer (HNC) patients with N1-lymph node status is not clarified. To assess the population-based effect of recent developments in radiotherapy such as intensity-modulated radiotherapy (IMRT) in relation to overall survival (OS) together with surgery in N1 HNC patients. We used 9,318 HNC cases with pT1/2 N0/1 disease from German cancer registries. Time of diagnosis ranged from January 2000 to December 2014, which we divided into three periods: (low [LIA] vs intermediate [IA] vs high [HIA] IMRT availability period) based on usage of IMRT in Germany. For each period, we examined a possible association between treatment (surgery vs. surgery and radiotherapy) in terms of OS. Statistical analyses included Kaplan-Meier and multivariate Cox regression (models adjusted for HPV-related cancer site). Temporal analysis revealed increasing usage of IMRT in Germany. In patients with N1 tumours, a comparison of patients treated with and without radiotherapy during the HIA period showed a superiority of the combined treatment as opposed to surgery alone (HR 0.54, 95%CI: 0.35-0.85, p = 0.003). The survival analyses related to treatments in terms of period underlined the superiority of surgery plus radiotherapy between periods IA and HIA (p = 0.03). The advent of IMRT, additional radiotherapy may present a survival advantage in patients with N1 HNC when combined with surgery.